Assessment of mineral intake in the diets of Polish postmenopausal women in relation to their BMI—the RAC-OST-POL study. Issue 1 (December 2016) - Głąbska, Dominika; Włodarek, Dariusz; Kołota, Aleksandra; Czekajło, Aleksandra; Drozdzowska, Bogna; Pluskiewicz, Wojciech
Abstract Background The diets of postmenopausal women in Western countries tend to be deficient in minerals, even if the energy value is at the recommended level. The objective of the presented population-based cohort study was to assess the intake of minerals (sodium, potassium, calcium, phosphorus, magnesium, iron, zinc and copper) in the diets of women aged above 55 years and to analyse the relations between BMI and mineral intake in this group. Methods The study was conducted in a group of 406 women who were randomly recruited from the general population of those aged above 55 years. The main outcome measures included BMI, reported sodium, potassium, calcium, phosphorus, magnesium, iron, zinc and copper intake assessed by dietary record (conducted during two typical, non-consecutive days). The distribution was verified with the use of the Shapiro-Wilk test. The comparison between groups was conducted using ANOVA with the LSD post hoc test or Kruskal-Wallis ANOVA with multiple comparisons. A comparison of satisfying nutritional needs was conducted using the chi-square test. Results Normal body weight individuals were characterised by lower sodium intake per 1000 kcal of diet than obese class II and III individuals (BMI ≥ 35.0 kg/m2 ). Overweight individuals were characterised by lower potassium and magnesium intake per 1000 kcal of diet than obese class I individuals (BMIϵ < 30.0; 35.0 kg/m2 ). The majority of individuals was characterised by insufficient potassium, calcium and magnesium intake. No differences in satisfying nutritional needs between BMI groups were observed for all minerals. Conclusions Following an improperly balanced diet was observed in the group of postmenopausal female individuals analysed. It was stated that the daily intake of all the assessed minerals was not BMI-dependent for the postmenopausal female individuals, but the nutrient density of diet (for sodium, potassium and magnesium) was associated with BMI.